Embryo culture in presence of oviductal fluid induces DNA methylation changes in bovine blastocysts - Barrera, Antonio Daniel (2017)
During the transit through the oviduct, the early embryo initiates an extensive DNA methylation reprogramming of its genome. Given that these epigenetic modifications are susceptible to environmental factors, components present in the oviductal milieu could affect the DNA methylation marks of the developing embryo. The aim of this study was to examine if culture of bovine embryos with oviductal fluid (OF) can induce DNA methylation changes at specific genomic regions in the resulting blastocysts. In vitro produced zygotes were cultured in medium with 3 mg/mL bovine serum albumin (BSA) or 1.25% OF added at the one- to 16-cell stage (OF1-16), one- to 8-cell stage (OF1-8) or 8- to 16-cell stage (OF8-16), and then were cultured until Day 8 in medium with 3 mg/mL BSA. Genomic regions in four developmentally important genes (MTERF2, ABCA7, OLFM1, GMDS) and within LINE-1 retrotransposons were selected for methylation analysis by bisulfite sequencing on Day 7-8 blastocysts. Blastocysts derived from OF1-16 group showed lower CpG methylation levels in MTERF2 and ABCA7 compared with the BSA group. However, CpG sites within MTERF2, ABCA7 and OLFM1 showed higher methylation levels in groups OF1-8 and OF8-16 than in OF1-16. For LINE-1 elements, higher CpG methylation levels were observed in blastocysts from the OF1-16 group than in the other experimental groups. In correlation with the methylation changes observed, mRNA expression level of MTERF2 was increased, while LINE-1 showed a decreased expression in blastocysts from OF1-16 group. Our results suggest that embryos show transient sensitivity to OF at early stages, which is reflected by specific methylation changes at the blastocyst stage.